The CEO code : create a great company and inspire people to greatness with practical advice from an experienced executive - Rohlander, David, 1941- (Career Press, 2013)
The CEO Code shows how to develop the attitudes, knowledge, skills, and behaviors required to master leadership and build a great company. This practical book shows you how to design your own program of development and create a masterpiece, personally and professionally. It is based on the wisdom gained from more than 30 years of business experience. Inspirational and informative, Rohlander shares real-life stories of success and failure from his personal journey and work as mentor and coach to CEOs and executives of Fortune 500 companies, mid-sized companies, and start-ups. The CEO Code will give you: -Practical advice for dealing with people -Proven strategies to increase business profits and growth -Unique and simple solutions to complex problems -The secret to authentic communications.